Critique of Judicial Scrutiny in the Restorative Justice Mechanism of the Draft Criminal Procedure Code - Prahassacitta, Vidya; Faraswati, Mega Ayu (Kosmik Hukum, 2026)
The article’s novelty serves critical analysis on the current legislative process concerning the restorative justice mechanism in the Draft Criminal Procedure Code that published in June 2025. The draft stipulates a restorative justice mechanism as a means of criminal case resolution outside of the courtroom. It requires critical evaluation because it undermines the central role of the judge which conducting checks and balances through Judicial Scrutiny over the processes carried out by other institutions, particularly the Police and the Prosecutor's Office. This study is aimed at answering the question: How should the restorative justice mechanism within the inquisitorial system be structured to provide protection for human rights? To address this question, we analysis using inquisitorial model system, and employ a comparative law approach to the Netherlands. The findings of this study indicate that the challenge of implementing a restorative justice mechanism in diverse social, cultural, economic and political contexts like Indonesia. The restorative justice can achieve the objective only if it is detached from the factor of power exercised by law enforcement officials. There is a necessity for professional mediators to fulfill the role of achieving consensus between the victim and the offender. The involvement of the Police and the Prosecutor is required in the initial stages to encourage the commencement of the restorative justice mechanism. However, the judge's role must be central; not only to formulize the agreement, but also actively assess, evaluate the execution of that agreement and even reopen the case should the agreement not be fulfilled.